Resiliensi Pegawai Dalam Menghadapi Beban Kerja Pada Pegawai Unit Penilaian Kompetensi Badan Kepegawaian Daerah - Fatimah Azzahra Putri Bachtiar; Khairani Zikrinawati; Ismi Nur Arifah (CV. ITTC INDONESIA, 2025)
This study aims to describe the forms of resilience and the influencing factors among employees at the Competency Assessment Unit of the Regional Civil Service Agency in dealing with high workloads. A descriptive qualitative approach was employed, with data collected through semi-structured interviews, observation, and literature review. Five informants were selected using purposive sampling, based on the criteria of having experienced or currently experiencing high workloads and their willingness to participate in the study. Thematic analysis was used to explore aspects of resilience reflected in the informants' experiences under work-related pressure. The findings indicate that analytical thinking is the most dominant aspect of resilience, as it significantly assists employees in formulating work strategies when facing demanding situations. Additionally, emotional regulation, self-efficacy, optimism, and goal orientation also play crucial roles in strengthening psychological endurance. Although impulse control and empathy were less dominant, both aspects still contribute meaningfully to maintaining healthy workplace relationships and fostering a supportive work environment. This resilience is shaped by professional experience, intrinsic motivation such as a sense of responsibility, personal satisfaction, and dedication to one’s work and is further reinforced by social support and a positive organizational culture. These findings highlight that strengthening resilience is a vital psychological strategy, not only for enhancing individual endurance but also for improving work performance and employee well-being in a comprehensive manner.